2019
DOI: 10.1080/10803548.2019.1688018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of musculoskeletal complaints among haemodialysis nurses – a comparison between Danish and Swedish samples

Abstract: The repetitiveness of priming and dismantling disposables for haemodialysis treatments might be an important contributor to musculoskeletal complaints. The objective was therefore to compare the prevalence of musculoskeletal complaints among haemodialysis nurses in Denmark and Sweden. Methods. For this cross-sectional study, nurses were recruited from haemodialysis centres in Denmark (n = 194) and Sweden (n = 351). Prevalence of musculoskeletal complaints was evaluated using the Nordic musculoskeletal question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
2
12
1
Order By: Relevance
“…The analysis of the most frequent symptoms reported by the interviewees shows that fatigue and headaches frequently affect professionals in the hemodialysis sector. This diverges from a recent study 14 that found that the most frequent symptoms were related to musculoskeletal disorders. It is possible that this difference 15 occurs because professionals in the sector are frequently exposed to ergonomic risks, such as stressful environment, work overload and understaffing.…”
Section: Methodscontrasting
confidence: 98%
“…The analysis of the most frequent symptoms reported by the interviewees shows that fatigue and headaches frequently affect professionals in the hemodialysis sector. This diverges from a recent study 14 that found that the most frequent symptoms were related to musculoskeletal disorders. It is possible that this difference 15 occurs because professionals in the sector are frequently exposed to ergonomic risks, such as stressful environment, work overload and understaffing.…”
Section: Methodscontrasting
confidence: 98%
“…Therefore, although there have been many studies and trial studies of various interventions aimed at preventing MSDs, current data still show a high prevalence of MSDs among nurses, even in countries with developed occupational disease prevention systems [ 22 24 ]. This raises questions about the effectiveness of these interventions and how to apply them effectively in the hospital setting for nurses.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MSDs worldwide is 20% to 33% [ 2 ]. It varies according to the type of activity [ 5 , 6 , 7 , 8 , 9 , 10 ] and affects both adolescents [ 11 ] and adults [ 5 ]. Teachers frequently present higher prevalence of MSDs, ranging from 39% to 95% [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%